Quantifying physiological differences between Brassica napus cultivars to identify traits to improve phosphorus uptake. - Batchelor, Alexandra (2023)
Phosphorus is an essential macronutrient for plants however many soils are phosphorus deficient. This leads to large scale application of phosphorus fertilisers which are non-renewable. An alternative to increasing phosphorus application would be to breed plants that are more efficient at taking up phosphorus from the soil. Brassica napus is the source of the second most produced vegetable oil worldwide and the primary source of edible vegetable oil in the European union and China. Its importance globally makes it important to future-proof it against declining availability of phosphorus fertilisers, this could be achieved through breeding new, more phosphorus efficient varieties.